PENGARUH KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Galih Chandra Kirana; Heriston Sianturi; Meifida Ilyas (Jurnal Liabilitas, 2023)
Tihis stuidy aiims to examinie tihe effeict of fuinding deciisions, diviidend poliicy, firm size, and profitability on the value of company. The population of the reseiarch iis 6i5 property, real estate, and building construction companies listed on the Indonesia Stock Exchange in the period 2018-2020. The sampling technique used was the purposive sampling method. Based on this method a sample size of 57 wais obtaiined, and aifter thie outilier wias isisued, the samiple siize became 40. The data analysis method used was multiple linear regression using SPSS software version 25. The result showed that firm size negatively affected the value of the company. While funding decisions, dividend policy, and profitability do not affect the value of company.